ACTIVE SEISMOTECTONIC STRUCTURES IN THE AREA OF CHIOS ISLAND, NORTH AEGEAN SEA, REVEALED FROM MICROSEISMICITY AND FAULT PLANE SOLUTIONS - Karakostas, V. G.; Papadimitriou, E. E.; Tranos, M. D.; Papazachos, C. B. (Bulletin of the Geological Society of Greece, 2010)
Data from a digital seismological network operating during April–July 2002 were used for the microseismicity study of the area around Chios Island (East Aegean Sea, Greece). Numerous microearthquakes were detected and more than 950 well–located hypocenters were obtained along with 96 reliably determined focal mechanisms. The epicentral distribution and focal mechanisms of several earthquakes revealed that the NE–SW striking dextral strike–slip faults dominate in the study area as is the dominant pattern in North Aegean Sea. An earthquake swarm near Psara Island and a cluster offshore the west coast of Chios Island are associated with NW–SE trending left–lateral strike–slip faults, orthogonal to the dextral ones. Near the west coast of the Island the microseismicity evidences that oblique faulting dominates, whereas onshore and offshore the North Chios Island, clusters of events manifest the activation of either E–W or N–S striking normal faults. This complex deformation pattern is the manifestation of the dextral strike–slip faulting termination against conjugate sinistral ones, the transition from strike–slip to normal through the oblique faulting, as well as the activation of biaxial normal faulting in places.